Book review: Sujit Kumar Chattopadhya, Gender Socialization and the Making of Gender in the Indian Context. (September 2019) - Sastry, Amrita
Sujit Kumar Chattopadhya, Gender Socialization and the Making of Gender in the Indian Context . New Delhi: SAGE Publications, 2018, pp. 274, ₹895, ISBN 978-93-866-0256-5 (Hardcover) .